Pengaruh Islamic Corporate Governance (ICG) dan Risk Taking Terhadap Tax Avoidance - Riduwan, Muhammad Fazar; Luthan, Luciana; Mazelfi, Ihsani (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
The purpose of this study is to determine and analyze the effect of Islamic Corporate Governance and risk taking on Tax Avoidance. The researcher took a case study on Islamic commercial banks in Indonesia in 2015-2019. The research sample amounted to 70 consisting of 14 Islamic Commercial Banks. The method used was purposive sampling. The data analysis method used multiple linear regression analysis tools. The Islamic Corporate Governance variable is determined by institutional ownership, audit committee and the number of sharia supervisory boards. The results of this study indicate that institutional ownership has a negative effect on tax avoidance, the audit committee has no effect on tax avoidance, the Sharia Supervisory Board has no effect on tax avoidance, risk taking has a significant effect on tax avoidance.